Pengembangan Aplikasi Inventory Produk Masker Camille Berbasis Web Menggunakan FIFO - Syifa Maulida Akmalia; Binastya Anggara Sekti; Nixon Erzed (Prosiding SISFOTEK, 2025)
Efficient inventory management plays a crucial role in store operations to prevent issues such as overstock, shortages, or product losses caused by expiration. Camille Beauty Store has faced challenges in handling stock manually, which is often inefficient and prone to human error. To address this problem, this study aims to design and implement a website-based inventory information system using the FIFO (First In, First Out) method to optimize stock management processes. The system was developed using PHP for the programming language and MySQL for database management, while the development stages followed the waterfall model, consisting of needs analysis, design, implementation, testing, and evaluation. Data collection was carried out through direct observations, interviews with the store owner, and literature studies to ensure system requirements were well-defined. The results demonstrate that the developed system successfully automates stock recording for both incoming and outgoing goods while applying the FIFO principle, ensuring older items are sold first to minimize the risk of expiration. In addition, the system provides real-time stock reporting, which supports management in making accurate and timely inventory- related decisions. The implementation of this system has proven to enhance efficiency, reduce manual errors, and accelerate reporting processes, although stable internet connectivity remains limitation.